2023
DOI: 10.1017/s1478951522001766
|View full text |Cite
|
Sign up to set email alerts
|

The expectations of metastatic cancer patients regarding palliative chemotherapy: A Brazilian–German qualitative study

Abstract: Objective To explore the expectations of Brazilian and German patients regarding metastatic cancer and palliative chemotherapy. Methods Interviews with 48 metastatic cancer patients from Brazil and Germany were conducted. The interviews were transcribed and analyzed using the thematic analysis approach to identify common themes. The sociodemographic data were collected using an instrument developed by the authors. Results A total of 48 patients participated in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Additionally, misconceptions of treatment goals by patients can be explained by coping strategies such as denial, which were well described in this patient population [36,37]. Overall, patients with advanced cancer often have overly optimistic expectations regarding their chances of survival and cure rates [3,5,34,38]. It is vital to understand treatment goals for patients so they can settle on more suitable decision-making aligned with their preferences and also be able to establish realistic expectations about treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, misconceptions of treatment goals by patients can be explained by coping strategies such as denial, which were well described in this patient population [36,37]. Overall, patients with advanced cancer often have overly optimistic expectations regarding their chances of survival and cure rates [3,5,34,38]. It is vital to understand treatment goals for patients so they can settle on more suitable decision-making aligned with their preferences and also be able to establish realistic expectations about treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The perception of curability is a crucial factor in the management of advanced cancer [1]. Previous studies have shown that oncologists tend to be more realistic in their assessment of curability [2][3][4], considering relevant clinical and scientific factors, while patients with advanced cancer may have unrealistic hopes and expectations regarding the possibility of a cure [5,6]. While oncologists rely on their clinical experience and the available scientific evidence to evaluate the potential cure, patients may have higher expectations of a cure, which could have been influenced by non-medical information and success stories of treatment [2,3].…”
Section: Introductionmentioning
confidence: 99%